Pendidikan Sufistik KH. Abdurrahman Wahid dan Relevansinya pada Kehidupan Masyarakat Era Digital - Muvid, Muhamad Basyrul (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2023)
The digital era provides wider space and a greater flow of change, which if not equipped with spiritual power, society can become liberal, materialistic, and secular. One way to strengthen the spiritual power of digital era society is through Sufistic education. Moderate Sufistic education that can harmonize spiritual and social forces as a human responsibility. Therefore, Sufistic thought is needed that describes this dimension, one of which is the thought of KH. Abdurrahman Wahid, so the focus of this research is trying to find and analyze KH's Sufsitic education. Abdurrahman Wahid and his relationship with digital society, both moral, spiritual, and social. The research method used is literature study, namely the study of literature from various books, journals, and other documentation regarding Gus Dur's Sufistic thought. The results obtained were that Gus Dur's Sufistic education prioritized humanistic aspects, so that the Sufism model seemed socialist and ethical, which was the key to fostering harmony, harmony and strength across differences. This strength leads to unity and unity of the people amidst existing differences. Then, Gus Dur's Sufistic education taught an open (tolerant) attitude and pluralism which could foster an attitude of moderation, justice and balance, so that it would not be easy to hurt other people's feelings, act anarchically, spread lies and provocation. For this reason, Gus Dur's Sufistic education model is very relevant to the situation and conditions of digital era society.